2011
DOI: 10.1007/s00586-011-1781-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative rehabilitation does not improve functional outcome in lumbar spinal stenosis: a prospective study with 2-year postoperative follow-up

Abstract: The aim was to study if postoperative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 44 publications
3
29
0
3
Order By: Relevance
“…11,56 The minimal changes in back and leg pain for our Education program are similar to findings in trials examining traditional postoperative physical therapy and prospective cohort studies. 1,8,39 Group differences at 3 month follow-up also support work by Abbott et al 3 that found a greater improvement in back pain after lumbar fusion with a 3 session psychomotor therapy program compared to exercise training.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…11,56 The minimal changes in back and leg pain for our Education program are similar to findings in trials examining traditional postoperative physical therapy and prospective cohort studies. 1,8,39 Group differences at 3 month follow-up also support work by Abbott et al 3 that found a greater improvement in back pain after lumbar fusion with a 3 session psychomotor therapy program compared to exercise training.…”
Section: Discussionsupporting
confidence: 70%
“…Randomized trials to date have found no significant difference between traditional physical therapy and either no treatment, an educational booklet, or advice to keep active. 1,46,51,52 These results suggest that an alternative approach to postoperative rehabilitation may be needed to address the psychosocial factors often associated with poor surgical spine outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Postsurgical supervised exercise was compared to home exercise or no exercise in two RCTs [13,14]. No differences were found in any of the outcomes, but due to the general benefits of exercise and patient preference, the recommendation favored postsurgical supervised exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Group B patients were only advised to stay active. No significant differenced were found between the groups regarding pain, ability to walk and satisfaction with undergone surgical treatment [13]. In this study the patients started physiotherapy as late as three months post surgery.…”
Section: Main Findingsmentioning
confidence: 58%
“…Gru pa A mia ła wdro żo ną fi zjo te ra pię trzy mie sią ce po le cze niu opera cyj nym, na to miast gru pa B mia ła tyl ko za le ce nie by być ak tyw ny mi. Nie stwier dzo no istot nych ró żnic po mię dzy gru pa mi do ty czą cych bó lu, mo żli wo ści cho dze nia i za do wo le nia z ope ra cji [13]. W ba daniach tych cho rzy roz po czę li fi zjo te ra pię do pie ro 3 mie sią ce po ope ra cji.…”
Section: Dys Ku Sjaunclassified